2012
DOI: 10.1104/pp.112.207746
|View full text |Cite
|
Sign up to set email alerts
|

Early Cone Setting in Picea abies acrocona Is Associated with Increased Transcriptional Activity of a MADS Box Transcription Factor    

Abstract: Conifers normally go through a long juvenile period, for Norway spruce (Picea abies) around 20 to 25 years, before developing male and female cones. We have grown plants from inbred crosses of a naturally occurring spruce mutant (acrocona). One-fourth of the segregating acrocona plants initiate cones already in their second growth cycle, suggesting control by a single locus. The early cone-setting properties of the acrocona mutant were utilized to identify candidate genes involved in vegetative-toreproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 39 publications
0
46
0
Order By: Relevance
“…Segregating siblings derived from inbred crosses of the acrocona mutant produce cones at a very early age (Uddenberg et al ., ). The early cone‐setting property of the acrocona mutation segregates as a single locus (Acheré et al ., ; Uddenberg et al ., ), but the mutation causing these traits has not yet been identified.…”
Section: Resultsmentioning
confidence: 99%
“…Segregating siblings derived from inbred crosses of the acrocona mutant produce cones at a very early age (Uddenberg et al ., ). The early cone‐setting property of the acrocona mutation segregates as a single locus (Acheré et al ., ; Uddenberg et al ., ), but the mutation causing these traits has not yet been identified.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these orthologues in P . abies have been shown to play key roles in cone development (Carlsbecker et al ., ; Uddenberg et al ., ). We found that the expression of eight MADS ‐ box genes ( PtDAL1 , PtDAL2 , PtDAL3 , PtDAL4 , PtDAL10 , PtDAL14 , PtMADS1 and PtMADS3 ) and PtNDLY were significantly higher in male structures of bisexual cones than in normal male cones (closest to maturity) (Figs , S9).…”
Section: Discussionmentioning
confidence: 97%
“…We identified spruce MADS‐box genes that are candidates for reproductive maturity or reproductive meristem identity in conifers (annotated as AGL20 (S uppressor of O verexpression of C onstans 1 ), SOC1‐like gene AGL42 and AGL2 ( SEPALLATA1 ) based on sequence homology with Arabidopsis genes) (Melzer et al ., ; Uddenberg et al ., ; Katahata et al ., ) which are paralogs of flowering genes in Arabidopsis . As there are no SEP1 genes in gymnosperms, the identified P. glauca gene WS00823_F11 is likely the ortholog of P. abies DEFICIENS AGAMOUS‐LIKE1 (PgMADS10_DAL1, with proposed function in regulating the transition from juvenile to adult phase in Picea ; Carlsbecker et al ., ), and which is located within the SEP1 sister clade more closely related to AGL6 .…”
Section: Discussionmentioning
confidence: 98%